Educational Lessons from the Stories of Moses-Aaron and Moses-Samiri in the Al-Tafsir Al-Hadith by Muhammad Izzat Darwazah: A Thematic Study of Qur’anic Childcare - Ach. Zayyadi; Fahmi (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2025)
Studies on child rearing from the perspective of the Qur'an tend to be normative and have not yet integrated a thematic interpretation approach that focuses on Qur'anic narratives. This gap indicates the need for studies that connect the moral lessons found in the stories of the prophets with contemporary child-rearing practices. This study aims to analyze the educational values contained in the stories of Moses and Aaron, as well as Moses and Samiri, in Tafsir al-Hadith by Muhammad Izzat Darwazah, and to explain their relevance to Islamic family education. This research employs a qualitative method based on library study, using thematic interpretation and content analysis approaches. The findings show that Darwazah’s interpretation, arranged according to the chronological order of revelation, integrates revelation, historical context, and educational values. The key values identified include strengthening faith, offering wise counsel, avoiding arrogance, and being cautious of misleading influences. These findings contribute to the development of a Qur'anic child-rearing model that balances spiritual, moral, and social dimensions within the context of contemporary Islamic family education.